Increased levels of leukocyte elastase in ischemic stroke and in subjects with vascular risk factors - Grau, Armin J.; Seitz, Rainer; Immel, Anette; Steichen-Wiehn, Christianne; Hacke, Werner (Cerebrovascular diseases, 1995)
Proteolytic enzymes by polymorphonuclear leukocytes such as elastase may contribute to the pathogenesis of acute cerebral ischemia. We measured elastase α1-protease inhibitor complexes (EIC) in acute ischemic stroke and in controls with and without vascular risk factors. Levels of EIC were higher in patients (n = 24, 51.4 ± 18.5 ng/ml) than in healthy controls (n = 26, 36.2 ± 11.5 ng/ml, p < 0.001) but not higher than in controls with risk factors (n = 22, 53.4 ± 29.6 ng/ml). Stroke patients with recent or concomitant infections had higher EIC levels than all other groups (n = 14, 71.0 ± 24.6 ng/ml). This result suggests leukocyte activation in acute stroke and in subjects with increased risk for stroke.